Synthesis of Water-Soluble Phthalocyanines and Modification of their Peripheral Fragments as a Method of Directed Changes in Lipophilic-Hydrophilic Properties - Kalashnikova, I.P.; Baulin, V.E. (Biomedical Chemistry: Research and Methods, 2018)
This article brief by describes results of studies devoted to synthesis of water-soluble phthalocyanines derivatives, which are carried out by the Complexing Agents Chemistry group of IPAC RAS. Metal-free ligands and metallophthalocyanines, containing peripheral substituents with fragments of pyridine, oxybenzoic and hydroxyphenylphosphonic acids are potential photosensitizers for photodynamic therapy of cancer diseases. Methods for the modification of peripheral substituents have been developed that make it possible to synthesize phthalocyanine ligands and complexes soluble in organic solvents, or soluble in aqueous media and also possess amphiphilic properties.